PEMBERIAN TUGAS DAN RESITASI UNTUK MENINGKATKAN HASIL BELAJAR MENGGAMBAR TEKNIK DASAR PADA SISWA SMK NEGERI 1 MERDEKA BERASTAGI - S, Natalia Barutu; Lubis, Asri (TABULARASA, 2013)
This study aims to improve the activity and learning outcomes Drawing Basic Technique class X at SMK Negeri 1 Merdeka Berastagi by applying Method Task Giving and recitation. The subjects were students of class X Architecture Engineering Skills program SMK Negeri 1 Berastagi Independent School Year 2012/2013 the number of students as many as 34 people, is a descriptive research method that aims to determine the average student learning outcomes at the time of the study conducted. Average student learning outcomes after the implementation of the method of administration tasks and recitation are increased, which from the first cycle the average value of student learning outcomes 72 increased to 85. So the increase in learning outcomes are achieved is 18.05%. From the results of research which aparted we get conclusion that activities dan result of learning increase with implemetation of the method of administration tasks and recitation.